The contours of police integrity - Haberfeld, M. R. (Maria R.), 1957-; Klockars, Carl B.; Kutnjak Ivković, Sanja, 1965- (Sage Publications, 2004)
Presenting a comprehensive overview of the potential for police misconduct worldwide, leading criminal justice scholars have compiled survey and case data from 10 countries chronicling police integrity and misconduct.